Relationship Between Job Characteristics, Job Satisfaction And Productivity In The Citarum River Restorationagencies, West Java,Republic Of Indonesia - Juhary, Ali; Owin Jamasy, Djamaludin (IOSR Journals, 2018)
It has been more than 30 years since the Government of Indonesia and the Regional Government of West Java Province carried out a program to restore the Citarum River, where the water was brown and dirty with garbage, and had chemical smell due to the domestic and chemical waste from the surrounding factories. The restoration work, which was focused solely on developing infrastructure, was proven ineffective in rehabilitating the river to its former and functioning role as an ecosystem for the living things nearby. Against this background, this study hypothesizes that the restoration work of the Citarum river can be more productive through the job design for the employees, namely job characteristics, in the Citarum restoration agencies.Thus this study was conducted on the relationship between job characteristics, job satisfaction and productivity amongst employess in the citarum restoration agencies in Bandung, Karawang and Bekasi, West Java. A sample of 283 respondents were collected and using SEM- analysis, the results of the studies indicated that the job characteristics and job satisfaction are the factors that have significant effects to increase the productivity in the restoration agencies of Citarum River with a value tvalue 4.42 (>1.96); whilst the job satisfaction variable has an influence on productivity with value tvalue 9.600 (>1.96). Thus the study concluded that the job design such as job characteristics with the increase in job satisfaction as a mediator has a significant effect on the productivity of employees in the restoration work of the Citarum River.